Taller de trabajo para mejorar la capacidad de diagnóstico de sistemas de producción de raíces y tubérculos : Memorias, Cartagena, septiembre 12-16, 1988 - Moreno, R.A. (International Center for Tropical Agriculture, 1989)
The papers presented at the workshop for improving the diagnostic capacity of root and tuber crop production systems are included as well as summaries of the discussion sessions and resulting recommendations. Participants came from Brazil, Ecuador, Mexico, Panama, Peru, Argentina, Colombia, Paraguay, Cuba, and Uruguay. The objectives of the workshop were to (1) determine the current status of activities carried out in each country to correctly diagnose production, utilization, and commercialization problems regarding root and tuber crops; (2) share experiences and results; (3) promote interest in the topic; and (4) identify research areas requiring further study. (CIAT)